Selenium status in term neonates, according to birth weight and gestational age, in relation to maternal hypertensive pathology - Bizerea-Moga, Teofana Otilia; Pitulice, Laura; Bizerea-Spiridon, Otilia; Angelescu, Claudiu; Mărginean, Otilia; Moga, Tudor Voicu (Frontiers in Pediatrics, 2023)
Background: Pregnancy represents a state of increased oxidative stress and antioxidants, in which selenium (Se) plays a pivotal role, contribute to maintain the oxidative balance. If antioxidant defenses are depleted, placental function is disrupted, resulting in pregnancy complications, including pregnancy-induced hypertension (PIH). Little is known about fetal selenium status in concomitant relation to maternal PIH, gestational age (GA) and birthweight (BW). Methods: We examined over a 3-year period the serum (SeS) and urine selenium (SeU) status in term neonates from normotensive (nonPIH) and hypertensive (PIH) mothers as clinical markers of oxidative stress. In this retrospective observational study, 72 neonates with maternal PIH were matched for GA and BW to 72 neonates of normotensive mothers. Four groups were obtained, based on maternal PIH and BW relative to GA (appropriate-for-gestational-age – AGA, small-for-gestational-age – SGA): nonPIH-AGA (control group), nonPIH-SGA, PIH-AGA, and PIH-SGA. Results: The results showed significant differences (p<0.001) in selenium levels among the study groups: SeS - 44.85±7.56 μg/L in nonPIH-AGA, 39.62±11.42 μg/L in nonPIH-SGA, 40.01±10.07 μg/L in PIH-AGA, and 25.39±8.99 μg/L in PIH-SGA; SeU - 27.98±7.99 μg/L in nonPIH-AGA, 22.85±9.48 μg/L in nonPIH-SGA, 23.44±6.73 μg/L in PIH-AGA, and 13.05±5.86 μg/L in PIH-SGA. Selenium depletion was more common in neonates born from hypertensive mothers and those born small for gestational age. Though moderate in intensity, selenium levels were positively correlated with BW (0.319 for SeS, 0.397 for SeU) and negatively correlated with maternal systolic blood pressure (-0.313 for SeS, -0.324 for SeU). The main independent effects on SeS and SeU of each maternal blood pressure and birth weight turned out statistically significant. In interaction, a more pronounced effect was reached in PIH-SGA neonates. Conclusion: Selenium status seemed to reflect the negative impact that PIH exerts in neonates during intrauterine development. Clinical markers of selenium status could thus be of great value for tracking responses of individuals to selenium supplementation as part of health improvement and harm mitigation approaches.